Work arrangements impact on employees job performance in the business process outsourcing: The case pf concentrix - Dela Cruz, Earvin John B.; Demafeliz, John Cris A.; Lozano, Evnney Rome J.; Ramonel, John Lester Y.; Regencia, Elijah Jean B. 4 0 16; 5
u
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2